2021
DOI: 10.3389/fendo.2021.754084
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Deformity and Gait Deviations Among Adolescents and Adults With X-Linked Hypophosphatemia

Abstract: BackgroundX-linked hypophosphatemia (XLH) is a rare genetic disorder characterized by lower limb deformity, gait and joint problems, and pain. Hence, quality of life is substantially impaired. This study aimed to assess lower limb deformity, specific radiographic changes, and gait deviations among adolescents and adults with XLH.DesignData on laboratory examination and gait analysis results were analyzed retrospectively. Deformities, osteoarthritis, pseudofractures, and enthesopathies on lower limb radiographs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
7
27
0
3
Order By: Relevance
“…Characteristically, XLH is associated with multi-apical lower limb deformities in different planes. Frontal plane deformities such as valgus or varus malalignment, often accompanied by sagittal diaphyseal bowing (procurvatum) have been described in this disorder recently ( 4 , 5 ). Less information is available on disorder-specific sagittal plane deformities, typically procurvatum deformity of the femur, tibia, and fibula and on transverse plane deformities of the lower limb [maltorsion of femur and tibia/fibula ( 21 )].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristically, XLH is associated with multi-apical lower limb deformities in different planes. Frontal plane deformities such as valgus or varus malalignment, often accompanied by sagittal diaphyseal bowing (procurvatum) have been described in this disorder recently ( 4 , 5 ). Less information is available on disorder-specific sagittal plane deformities, typically procurvatum deformity of the femur, tibia, and fibula and on transverse plane deformities of the lower limb [maltorsion of femur and tibia/fibula ( 21 )].…”
Section: Discussionmentioning
confidence: 99%
“…Less information is available on disorder-specific sagittal plane deformities, typically procurvatum deformity of the femur, tibia, and fibula and on transverse plane deformities of the lower limb [maltorsion of femur and tibia/fibula ( 21 )]. Although the need for lower limb deformity analysis in the evaluation of XLH patients was mentioned in several studies ( 4 , 5 , 9 ), detailed quantitative radiographic data on the influence of pharmacological treatment on lower limb development is lacking. Linglart et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High BMI has been reported in other studies of populations of patients with XLH. One third of children in an XLH population in France were reported to be overweight or obese [30], and adolescents and adults with XLH in Austria had a mean elevated BMI, with 35.0% reported as being overweight and 30.0% as obese [31]. However, data collected in this registry have shown that children and adults combine shorter stature with 'normal' weight, leading to an elevated BMI.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, XLH has lifelong clinical consequences such as short stature, musculoskeletal pain, complex skeletal deformities, disability among adults, premature osteoarthritis (OA) and enthesopathies ( 1 3 ). Lower limb deformities frequently occur in children and adolescents with XLH ( 4 , 5 ) possibly caused by changes in bone growth and/or surgical interventions ( 4 ). The skeletal deformities lead to impaired gait and decreased quality of life (QoL), which are associated with a high burden of disease in XLH patients ( 1 3 ).…”
Section: Introductionmentioning
confidence: 99%